2014
DOI: 10.1016/j.jneumeth.2014.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Using the readiness potential of button-press and verbal response within spoken language processing

Abstract: h i g h l i g h t s• Detection of readiness potential onset represents a preconscious measure for end-of-turn anticipation in a language dialogue.• Even if it is a language task it can be applied equally well to both verbal and finger movement responses.• In contrast to behavioural reaction time tasks the EEG-measurement produces more reliable data for the anticipation performance in end-of-turndetection.a r t i c l e i n f o New method: The purpose of this study was to examine if readiness potentials (RP) can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…A similar conclusion was drawn from two recent EEG studies (Jansen, Wesselmeier, De Ruiter, & Mueller, 2014;Wesselmeier, Jansen, & Müller, 2014) using a known ERP component, the Readiness Potential (RP) or Bereitschaftspotential (Kornhuber & Deecke, 1965), a slow negative-going cortical potential associated with the preparation of voluntary movements. Participants heard materials recorded by an instructed speaker, rather than being extracted from conversational corpus materials as used in the studies cited in the previous paragraph.…”
Section: Speaking On Timesupporting
confidence: 71%
See 1 more Smart Citation
“…A similar conclusion was drawn from two recent EEG studies (Jansen, Wesselmeier, De Ruiter, & Mueller, 2014;Wesselmeier, Jansen, & Müller, 2014) using a known ERP component, the Readiness Potential (RP) or Bereitschaftspotential (Kornhuber & Deecke, 1965), a slow negative-going cortical potential associated with the preparation of voluntary movements. Participants heard materials recorded by an instructed speaker, rather than being extracted from conversational corpus materials as used in the studies cited in the previous paragraph.…”
Section: Speaking On Timesupporting
confidence: 71%
“…Participants heard materials recorded by an instructed speaker, rather than being extracted from conversational corpus materials as used in the studies cited in the previous paragraph. The first study (Jansen et al, 2014) used both a button-press and a spoken-response paradigm, in which participants were asked to give a short verbal answer (yes or no). In both tasks, an RP was found to start almost 1,200 milliseconds before the response.…”
Section: Speaking On Timementioning
confidence: 99%
“…In exploring the two results of this study in combination with previous research on the RP development turn-taking [7], response preparation of formulated sentences delays the RP-onset compared to the simple verbal cue "Ja" (yes) as a response. However, both short and long RTs caused the same RP-onset to response interval, indicating different time intervals for the response decision, but the same intervals for response preparation (lexical selection, lemma and phonological retrieval).…”
Section: Discussionmentioning
confidence: 94%
“…during anticipation [7] have shown that the response-locked RP of vocal onset is similar to RP of a button-press. This evidence means that a voice-related RP-onset can be used for motor preparation in the same manner as it is used for button-press and is not affected by breathing in or other preparation factors for verbalization.…”
mentioning
confidence: 95%
“…In an electroencephalographic (EEG) study with German sentence stimuli, participants were instructed to press a button exactly at the moment an aurally presented sentence ended. A lateralized readiness potential related to the button press was observed 600 to 800 milliseconds before the end of the sentences, indicating that participants were aware of the sentence end 600 to 800ms before it actually ended [22]. Although only based on aural clues, this early anticipation leaves plenty of time for the listener to prepare their own turn and allows the turn transition to be smooth.…”
Section: Introductionmentioning
confidence: 94%